Analysis of Self-Harm Behavior in Islamic Psychology: Trends, Impact, and Future Research Directions through Bibliometric Study - Azmil Iman hartafan (Bulletin of Islamic Research, 2023)
This study aims to conduct a bibliometric analysis related to self-harm behavior in Islamic psychology. The bibliometric analysis technique is used to browse all publications indexed in the Scopus database and the data obtained is analyzed using Excel, R-studio, and VOSviewer. This research method involves searching and analyzing scientific articles related to Islamic psychology such as keywords, number of publications per year, key data information, number of citations, prolific researchers, and place of publication related to this study, to provide an understanding of the development and impact of research in this field. The results of the bibiometric analysis show that self-harm behavior in Islamic psychology has become an increasing subject of research in recent years as well as a significant increase in the number of publications in this field. The limitation of this study is that it only takes datasets or metadata of publications indexed in Scopus. Other national and international databases were not considered in this study. This study presents a brief overview of the literature that researchers can access and provides recommendations for future research.